2021
DOI: 10.1016/j.eprac.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

American Association of Clinical Endocrinology Clinical Practice Guideline: The Use of Advanced Technology in the Management of Persons With Diabetes Mellitus

Abstract: automated insulin dosing continuous glucose monitoring continuous subcutaneous insulin infusion diabetes diabetes technology glucose sensors hybrid closed loop insulin pumps sensor-augmented pump low-glucose suspend predictive low-glucose suspend a b s t r a c t Objective: To provide evidence-based recommendations regarding the use of advanced technology in the management of persons with diabetes mellitus to clinicians, diabetes-care teams, health care professionals, and other stakeholders. Methods: The Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
160
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 342 publications
(323 reference statements)
0
160
0
13
Order By: Relevance
“…Alongside this, the development of continuous subcutaneous insulin infusions (CSII) systems combined with sensoraugmented pump therapy (SAP) and potentially hybrid closed-loops (HCL) systems to respond to changes in HbA1c levels thereby further reducing episodes of hypoglycaemia (Garg et al, 2017;Karges et al, 2017;Steineck et al, 2017;Burckhardt et al, 2018;Gómez et al, 2018;Korkmaz et al, 2018;Stone et al, 2018;Grunberger et al, 2021;Moreno-Ferández et al, 2021;Roze et al, 2021). There can though be concerns with the extent of patient benefits with CSII systems over multiple daily injections; however, again this is not universal (Mueller-Godeffroy et al, 2018;Blair et al, 2019).…”
Section: Developments In Insulin Administration and The Implicationsmentioning
confidence: 99%
“…Alongside this, the development of continuous subcutaneous insulin infusions (CSII) systems combined with sensoraugmented pump therapy (SAP) and potentially hybrid closed-loops (HCL) systems to respond to changes in HbA1c levels thereby further reducing episodes of hypoglycaemia (Garg et al, 2017;Karges et al, 2017;Steineck et al, 2017;Burckhardt et al, 2018;Gómez et al, 2018;Korkmaz et al, 2018;Stone et al, 2018;Grunberger et al, 2021;Moreno-Ferández et al, 2021;Roze et al, 2021). There can though be concerns with the extent of patient benefits with CSII systems over multiple daily injections; however, again this is not universal (Mueller-Godeffroy et al, 2018;Blair et al, 2019).…”
Section: Developments In Insulin Administration and The Implicationsmentioning
confidence: 99%
“…However, the ADA acknowledged that physicians’ opinions can vary when prescribing CSII, with some recommending pump therapy for motivated PwD with daily schedules unsuited to MDI, and others only endorsing prescription when treatment with MDI fails to achieve glycemic control [ 33 ]. A further consensus statement published in 2021 by the American Association of Clinical Endocrinologists/American College of Endocrinology (AACE/ACE) indicated that CSII should only be provided if the prescribing practice can offer a comprehensive pump management program for PwD [ 34 ]. Moreover, the AACE/ACE emphasized appropriate patient selection with a thorough assessment of the individual’s knowledge of diabetes management principles [ 34 ].…”
Section: Diabetes Technologies and Their Applicationsmentioning
confidence: 99%
“…A further consensus statement published in 2021 by the American Association of Clinical Endocrinologists/American College of Endocrinology (AACE/ACE) indicated that CSII should only be provided if the prescribing practice can offer a comprehensive pump management program for PwD [ 34 ]. Moreover, the AACE/ACE emphasized appropriate patient selection with a thorough assessment of the individual’s knowledge of diabetes management principles [ 34 ]. Combination of these guidelines and position statements indicate the ideal CSII candidate as an individual with T1D currently performing four or more insulin injections and SMBG tests per day, who is motivated to achieve optimal glycemic control, and is willing and able to carry out the tasks associated with CSII safely and effectively, while maintaining frequent contact with their healthcare team [ 30 , 34 , 35 ].…”
Section: Diabetes Technologies and Their Applicationsmentioning
confidence: 99%
See 2 more Smart Citations